Proceedings of the 2011 ACM SIGMOD International Conference on Management of Data 2011
DOI: 10.1145/1989323.1989338
|View full text |Cite
|
Sign up to set email alerts
|

Designing and refining schema mappings via data examples

Abstract: A schema mapping is a specification of the relationship between a source schema and a target schema. Schema mappings are fundamental building blocks in data integration and data exchange and, as such, obtaining the right schema mapping constitutes a major step towards the integration or exchange of data. Up to now, schema mappings have typically been specified manually or have been derived using mapping-design systems that automatically generate a schema mapping from a visual specification of the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 21 publications
(35 reference statements)
1
95
1
Order By: Relevance
“…AttV may also be 2 This form of feedback is called negative relevance feedback in the information retrieval literature [47]. retrieved from the sources in which case provenance = Map, where Map is the set of mappings that can be used to retrieve AttV from the sources.…”
Section: Candidate Mappings and User Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…AttV may also be 2 This form of feedback is called negative relevance feedback in the information retrieval literature [47]. retrieved from the sources in which case provenance = Map, where Map is the set of mappings that can be used to retrieve AttV from the sources.…”
Section: Candidate Mappings and User Feedbackmentioning
confidence: 99%
“…We then select the mappings that maximize the recall with a given precision threshold λ p , i.e., the mappings that maximize the evaluation function eval recall in equation (2). To do this, we used NOMADm 10 , an implementation of the Mesh Adaptive Direct Search algorithm [1].…”
Section: Experimental Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been much research in schema mapping, from the seminal work on Clio [10], which provided a practical system and furthered the theoretical foundations of data exchange [11] to more recent systems that support additional schema constraints [17]. Alexe et al [1] generate schema mappings from examples of source data tuples and the corresponding tuples over the target schema. Karma [13] and An et al [2] generate mappings into ontologies, suggested by exploring low-cost Steiner trees that connect matching semantic types within a graph derived from the target ontology.…”
Section: Related Workmentioning
confidence: 99%
“…Although desirable, generating these descriptions automatically is a challenging problem [1,7,10,17,20]. Most of the proposed approaches on the Semantic Web focus on the first step of the modeling process.…”
Section: Introductionmentioning
confidence: 99%